Creative and innovative network management - Popov, Oliver Blagoj, 1953- (NATO science series. Computer and systems sciences, 2003)
Networking methods and the needs for competence demand flexibility and adaptability of the education systems. This text argues that every country's authority should promote networking throughout the education process in order to create a suitable environment for life-long learning.